Circumventing the WHO Code? An observational study. Issue 4 (29th June 2011) - Berry, Nina J; Jones, Sandra C; Iverson, Don
Abstract : Background: This study compares the formula milk advertisements that appeared in parenting magazines published in two countries that have enacted measures to restrict the advertising of infant formula products in response to the international code with two that have not. Methods: Content analysis was used to compare the type and frequency of formula milk advertisements that appeared in parenting magazines collected from the USA, Canada, the UK and Australia during 2007, and to examine whether there was a relationship between these frequencies and advertising regulations. Findings: Advertisements that promoted formula products or brands occurred in all of the magazines sampled but the type of product advertised differed. Follow-on formula advertisements occurred more frequently in titles from the UK, where infant formula advertising is prohibited (RR 3.82, 95% CI 2.65 to 5.50, p<0.0001) than they did in titles from the USA/Canada where infant and/or follow-on formula advertising is permitted. Toddler milk advertisements appeared more frequently in titles from Australia, where infant and follow-on formula advertising is prohibited, than they did in titles from countries where direct-to-consumer infant and/or follow-on formula advertising is permitted. Rate ratios were as follows: UK only 0.03 (95% CI 0.01 to 0.11, p<0.0001); USA/Canada only 0.02 (95% CI 0.01 to 0.06, p<0.0001). Interpretation: Bans on the advertising of infant formula products do not prevent companies from advertising (follow-on or toddler formula). These products are presented in ways that encourage consumers to associate the claims made in them with a group of products (a product line) that includes infant formula.